Randomized controlled trial of adjunctive Valproate for cognitive remediation in early course schizophrenia. (November 2019) - Ibrahim, Ibtihal; Tobar, Salwa; Fathi, Warda; ElSayed, Hanan; Yassein, Amal; Eissa, Ahmed; Elsheshtawy, Eman; Elboraei, Hala; Shahda, Mohamed; Elwasify, Mahmoud; Ibrahim, Ahmed; Chen, Kehui; et al.
Abstract: Background: Schizophrenia (SZ) is associated with cognitive impairment that contributes to disability, but the cognitive dysfunction is relatively refractory to pharmacologic intervention. Though Valproate augmentation is reported to improve psychopathology among patients with SZ, its effects on cognitive functions have not been investigated systematically. Methods: Using a randomized double blind placebo controlled design, the effects of Valproate or placebo as adjuncts to risperidone (RISP) treatment were evaluated among patients with early course SZ (N = 109). Domains of cognitive function, estimated using the Arabic version of the Penn Computerized Neurocognitive Battery, were the prime outcomes. Clinical severity and social function were secondary outcomes. We also explored the effects of valproate treatment on serological responses to Toxoplama Gondii (TOXO), a putative risk factor for cognitive dysfunction in SZ. Results: There were no significant differences between Valproate and placebo (PLA) treated groups with respect to changes in cognitive functions, positive or negative symptom scores or daily function scores at the beginning and end of the study. No significant Valproate/PLA differences were noted on TOXO serostatus or TOXO-related cognitive dysfunction. Conclusion: Valproate treatment may not be beneficial for cognitive dysfunction in SZ or for TOXO infection.